LANGUAGE ACQUISITION OF DOWN SYNDROME CHILDREN IN THE DOWN SYNDROME VILLAGE PONOROGO : A PSYCHOLINGUISTICS OVERVIEW - Sumarlam, Sumarlam; Purnanto, Dwi; Pamungkas, Sri; Hasyim, Khoirul; Utami, Angga Cahyaning (PRASASTI: Journal of Linguistics, 2016)
This study focused on language acquisition of down syndrome children in the down syndrome village Ponorogo, East Java, Indonesia. The down syndrome villages are Krebet sub-district of Jambon, Sidoharjo sub-district of Jambon, Karangpatihan sub-district of Sidoharjo, Pandak sub-district of Balong, and Dayakan sub-district Badegan.            The purpose of this study were (1) to explain the first language acquisition, in both lexical and grammatical; (2) to explain the second language acquisition, both lexical and grammatical; (3) to explain the factors that affect language acquisition of down syndrome children in Ponorogo, East Java, Indonesia. The method used in this study include the data providing by interview and questionnaire; the data are analyzed descriptively by stages identifying, classifying, interpreting, and explicating.            The results showed that the down syndrome children aged 7-15 years which were being the research object, mastering the first language (mother tongue) only, it is Javanese in the ngoko form (the Javanese language lowest level). They do not mastered Bahasa Indonesia as the second language as well. The first language acquisition of lexical mastery are in the unique forms, including the mention of an object by a unique form, e.g. knife called pangot, the mention of the object based on its sound (onomatopoeic), for example ‘eong’ to mention cat, elimination of beginning consonants and vowels, elimination of middle consonant, consonant replacements, and others. Down syndrome children did not acquire prefix and also the repetition, did not recognize compound words, the concepts which are mastered is the here and now, the things around him, and now, it is not the past and imagination. In addition, children with Down syndrome do echolalia (imitating others), autoecholalia (repeating his own words), verbal auditory agnosia or cogenital word deafness (phonological perception problem). Some informants also impaired speech or stuttering and selective mutism (not speaking to certain situations and places)            The down syndrome children were studied experienced those cases above since their birth, although some of them had the problems because of high temperature when they were on 6 months, 1.5 years, and 2 years. Inbreeding, maternal age over 35 years, and malnutrition becomes a trigger of down syndrome. The factors that affect the first and second language acquisition are (1) the informant is rarely communicate; (2) the informant never be read bedtime stories before bed; (3) the informant had not been provided the singing before bed; (4) The lack of attention from the family toward education, especially language acquisition. Key words      : language acquisition, down syndrome children, psycholinguistic